Effects of Age at Onset and Years of Musical Training on Consonant Recognition in Musicians - Ebtesam Sajjadi; Ahmadreza Nazeri; Ali Mohammadzadeh; Nooshin Sayadi; Saeid Farahani; Ghassem Mohammadkhani (Auditory and Vestibular Research)
Background and Aim: Previous research has shown that musicians have better performance in consonant recognition in noise compared to non-musicians. This study aimed to determine the effects of age at onset and years of musical training on consonant recognition in noise in musicians. Methods: Thirty-six Persian-speaking young musicians with normal hearing whose age at onset of musical training ranged 4–8 years and had at least 10 years of musical training, were asked to listen to Consonant-Vowel-Consonant (CVC) tokens presented in 12-talker babble noise and transcribe them. Multiple linear regression analysis was used to determine the ability of age at onset of musical training and years of musical training in predicting the recognition of stops and fricatives. Results: The age at onset of musical training significantly predicted consonant recognition in noise (p<0.001, R2= 0.614), while years of musical activity had no significant effect (p=0.055). Conclusion: Early start of musical training seems to improve the ability to recognize consonants in challenging listening environments.